2021
DOI: 10.1097/md.0000000000025498
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and forecasting of respiratory viral epidemics among children in west China

Abstract: We aimed to assess the respiratory virus characteristics and forecasts among young children with acute respiratory tract infection (ARTI) in west China. This retrospective study investigated the epidemic characteristics of respiratory viruses among 11,813 paediatric ARTI patient samples (mean age, 2.25 years) between March 2018 and March 2020. The ratio of boys to girls was 1.36. The 2 predominant viruses were influenza (Flu) A and respiratory syncytial virus (RSV) in both years, with Flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
2
7
1
Order By: Relevance
“…In this study, a cohort of infants and young children with acute respiratory tract infections between January 2019 and March 2020 was established. RSV was detected in about 15% of patients in this cohort (Supplementary Table 1), which was comparable to RSV incidences reported for Shanghai (Liu et al, 2018;Zhao et al, 2019) and slightly lower than elsewhere in China (Yu et al, 2019;Duan et al, 2021;Sun et al, 2021). Number of RSV-A-infected cases was slightly higher than RSV-B, but the clinical profiles of RSV-A-positive and RSV-B-positive cases were highly similar: infection by either type was significantly associated with patient age younger than 1 year, absence of fever, and presence of wheezing/gasping symptoms (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, a cohort of infants and young children with acute respiratory tract infections between January 2019 and March 2020 was established. RSV was detected in about 15% of patients in this cohort (Supplementary Table 1), which was comparable to RSV incidences reported for Shanghai (Liu et al, 2018;Zhao et al, 2019) and slightly lower than elsewhere in China (Yu et al, 2019;Duan et al, 2021;Sun et al, 2021). Number of RSV-A-infected cases was slightly higher than RSV-B, but the clinical profiles of RSV-A-positive and RSV-B-positive cases were highly similar: infection by either type was significantly associated with patient age younger than 1 year, absence of fever, and presence of wheezing/gasping symptoms (Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…As known, RSV and PIV3 are the most prevalent viruses in patients with ARI in China (1,(4)(5)(6)16). In the viral coinfection cohort, the most frequently co-detected virus was RSV (60.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Parainfluenza Viruses (PIVs) can cause various respiratory infections, ranging from mild upper respiratory illnesses in healthy adults to croup, bronchiolitis, pneumonia in infants and children, and severe lower respiratory infections in elderly and immunocompromised people (3). In China, Parainfluenza Virus type 3 (PIV3) is the most virulent of the four PIV serotypes, accounting for 60 -70% of primary PIV infections, and the PIV3 infection frequency is approximately 2.56 -10.9% (1,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown that controlling the spread of respiratory viruses is conducive to the growth and development of children. Since the immune and respiratory systems of infants and preschool children are not yet mature, early viral respiratory tract infections may have an adverse effect on lung development and increase the risk of incident asthma ( 10 ). ARTIs caused by viruses are the major cause of death and illness among children under 5 years of age ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our research group collected relevant data and analyzed the epidemiological characteristics of ARTIs caused by respiratory viruses in children before the outbreak of COVID-19 ( 10 ). At present, few studies have shown the epidemiology of respiratory viruses in children during the COVID-19 epidemic, and the incidence, age of onset, and seasonal changes in respiratory viruses in children remain unclear.…”
Section: Introductionmentioning
confidence: 99%